Genetic Interactions between the Chlorate-Resistant Mutant cr 8 8 and the Photomorphogenic Mutants cop1 and hy5 - Cao, Dongsun (American Society of Plant Biologists, 2000)
The chlorate-resistant mutant cr88 is defective in photomorphogenesis, as shown by the phenotypes of long hypocotyls in red light and yellow cotyledons under all light conditions. A subset of light-regulated genes is expressed at subnormal levels in cr88. To analyze further the role that CR88 plays in photomorphogenesis, we investigated the genetic interactions between cr88 and mutants of two other loci affecting photomorphogenesis, CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) and LONG HYPOCOTYL5 (HY5). COP1 represses the expression of light-regulated genes in the dark, and HY5 inhibits hypocotyl elongation in the light. Using morphological, cellular, and gene expression criteria for epistasis analyses to position CR88 in the genetic hierarchy of the photomorphogenesis pathway, we determined that CR88 acts downstream of COP1 but in a branch separate from HY5. In the course of our analysis, we discovered that light causes extensive destruction of plastids in dark-grown cop1 seedlings and that cr88 prevents this destruction.